European guidelines on microscopic colitis: United European Gastroenterology and European Microscopic Colitis Group statements and recommendations. Issue 1 (22nd February 2021) - Miehlke, Stephan; Guagnozzi, Danila; Zabana, Yamile; Tontini, Gian E.; Kanstrup Fiehn, Anne‐Marie; Wildt, Signe; Bohr, Johan; Bonderup, Ole; Bouma, Gerd; D'Amato, Mauro; Heiberg Engel, Peter J.; Fernandez‐Banares, Fernando; et al.
Abstract: Introduction: Microscopic colitis is a chronic inflammatory bowel disease characterised by normal or almost normal endoscopic appearance of the colon, chronic watery, nonbloody diarrhoea and distinct histological abnormalities, which identify three histological subtypes, the collagenous colitis, the lymphocytic colitis and the incomplete microscopic colitis. With ongoing uncertainties and new developments in the clinical management of microscopic colitis, there is a need for evidence‐based guidelines to improve the medical care of patients suffering from this disorder. Methods: Guidelines were developed by members from the European Microscopic Colitis Group and United European Gastroenterology in accordance with the Appraisal of Guidelines for Research and Evaluation II instrument. Following a systematic literature review, the Grading of Recommendations Assessment, Development and Evaluation methodology was used to assess the certainty of the evidence. Statements and recommendations were developed by working groups consisting of gastroenterologists, pathologists and basic scientists, and voted upon using the Delphi method. Results: These guidelines provide information on epidemiology and risk factors of microscopic colitis, as well as evidence‐based statements and recommendations on diagnostic criteria and treatment options, including oral budesonide, bile acid binders, immunomodulators and biologics. Recommendations on the clinical management of microscopic colitis are provided based on evidence, expert opinion and best clinical practice. Conclusion: These guidelines may support clinicians worldwide to improve the clinical management of patients with microscopic colitis.